2016
DOI: 10.1155/2016/6485343
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Antigen 75 Polymorphisms Are Associated with Disease Susceptibility and Phenotype in Japanese Patients with Inflammatory Bowel Disease

Abstract: Recent genome-wide association studies have rapidly improved our understanding of the molecular pathways leading to inflammatory bowel disease (IBD), which includes Crohn's disease (CD) and ulcerative colitis (UC). Although several reports have demonstrated that gene single nucleotide polymorphisms (SNPs) are associated with susceptibility to IBD, its precise genetic factors have not been fully clarified. Here, we performed an association analysis between lymphocyte antigen 75 (LY75) genetic variations and IBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…The remaining two significant variants in this locus are less common and are located in the nearby gene LY75 encoding the protein lymphocyte antigen 75. rs114821641-T causes a stop-gain mutation and an increase in suPAR (effect = 0.400; P = 1.08 × 10 −13 , EAF = 0.003), and rs755902185 is a deletion which causes a frameshift mutation in LY75 and an increase in suPAR (effect = 0.445; P = 1.05 × 10 −9 , EAF = 0.0004). Variants in LY75 have previously been associated with Inflammatory Bowel Syndrome and Crohn’s disease 36 , 37 . GO terms biological processes associated with the gene include endocytosis, immune response, and inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining two significant variants in this locus are less common and are located in the nearby gene LY75 encoding the protein lymphocyte antigen 75. rs114821641-T causes a stop-gain mutation and an increase in suPAR (effect = 0.400; P = 1.08 × 10 −13 , EAF = 0.003), and rs755902185 is a deletion which causes a frameshift mutation in LY75 and an increase in suPAR (effect = 0.445; P = 1.05 × 10 −9 , EAF = 0.0004). Variants in LY75 have previously been associated with Inflammatory Bowel Syndrome and Crohn’s disease 36 , 37 . GO terms biological processes associated with the gene include endocytosis, immune response, and inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…L1CAM regulates microRNAs associated with inflammation and progression of Alzheimer's disease and Parkinson's disease [ 111 ]. Lymphocyte antigen 75 (LY75) polymorphisms are associated with susceptibility and phenotype of inflammatory bowel disease [ 112 ]. MUC1 promotes chronic inflammation and cancer [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has reported that the expression of CD209 on macrophages activates phagocytosis, mediates DC rolling interactions with endothelium, activates CD4 + T cells and initiates innate immunity by modulating TLRs [53, 54]. LY75 expressed on CD8 + DCs plays a role in antigen processing and presentation in the context of both MHC class I and class II molecules and generates T helper 1-mediated immune responses through an IL-12-independent and CD70-dependent mechanism [55]. The roles of those C-type lectins need to be confirmed in T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%